2011
DOI: 10.1007/s11814-010-0525-8
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Ergun equation for application in trickle bed reactors randomly packed with trilobe particles using computational fluid dynamics technique

Abstract: Based on a slit model, a pellet scale model has been developed for calculation of drag force imposed on trilobe catalyst particles in a packed bed reactor. The drag coefficient for single gas phase flow in a porous media has been calculated by CFD simulation and the results compared to the Ergun equation. The results show that the drag coefficient predicted by Ergun equation should be modified for various bed porosities, particle aspect ratio and gas densities. Therefore, a correction factor has been proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…To this goal, a rectangular bed is investigated. To allow a comparison between the results in this study and their reported data, the loading methods (sock and dense), catalyst type, and catalyst size are identical to the data in [31,32]. On the other hand, these two parameters are important in trickle-flow modeling [30].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…To this goal, a rectangular bed is investigated. To allow a comparison between the results in this study and their reported data, the loading methods (sock and dense), catalyst type, and catalyst size are identical to the data in [31,32]. On the other hand, these two parameters are important in trickle-flow modeling [30].…”
Section: Introductionmentioning
confidence: 89%
“…In order to determine the influence of sharp corners on reactor pressure drop, simulation and experimental results for a rectangular bed were compared to experimental results from Bazmi et al [38] for a cylindrical bed (diameter: 0.12 m, height: 1 m). Fig.…”
Section: Influence Of Sharp Cornersmentioning
confidence: 99%
“…Many researchers have previously shown that these mass flux ranges would create a trickling flow regime in trickle bed reactors [34,35]. Supplementary details about this experimental setup have been previously reported by Bazmi et al [36]. The industrial alumina trilobe catalyst which has a diameter of 1 mm and an average length of 4.2 mm is used in the reactor bed.…”
Section: Methodsmentioning
confidence: 98%
“…The variety of particle shapes, operating modes of the packed bed devices, physicochemical properties of substances leads to the fact that the scientific literature has a wide variety of modified equations for determining the pressure drop in the packed beds . The traditional approach to the analytical calculation of pressure drop in the fixed‐bed apparatus filled with particles of various shapes is based on the Ergun equation and its various modifications: normalΔpL=150μDp2()1normalɛ2normalɛ3vs+1.75ρDp21ɛnormalɛ3vs2 where |Δ p | is the pressure drop in the packed bed for the length L ; μ is the viscosity; ρ is the density; v s is the superficial velocity (i.e., the velocity that the fluid would have through the empty tube at the same volumetric flow rate); ɛ is the void fraction of the bed (interparticle porosity); D p is the mean particle diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The variety of particle shapes, operating modes of the packed bed devices, physicochemical properties of substances leads to the fact that the scientific literature has a wide variety of modified equations for determining the pressure drop in the packed beds. [15][16][17] The traditional approach to the analytical calculation of pressure drop in the fixed-bed apparatus filled with particles of various shapes is based on the Ergun equation 13 and its various modifications [18][19][20][21] :…”
Section: Introductionmentioning
confidence: 99%